Evaluation of the Religious Development of Students at SMK Al-Azhar Batam in Building Spiritual Awareness Based on Religious Dimensions - Asep Nursobah; Arjuna Arjuna; Figo Prilianto; Mutiara Ariska; Melinda Koestanti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study evaluates the effectiveness of religious development programs at SMK Al-Azhar Batam in fostering students' spiritual awareness using the framework of religious dimensions. The primary aim is to assess how these structured programs instill spiritual consciousness, ensuring students internalize and practice Islamic values as intrinsic daily elements. This research addresses a gap in prior studies that focused mainly on discipline and autonomy. Employing a qualitative field research approach with descriptive methods, the study focused on students and program coordinators at SMK Al-Azhar Batam as subjects. Primary data were collected through semi-structured interviews with teachers or coordinators and direct observations during religious activities. Data analysis followed Miles and Huberman's model. Findings indicate that programs (communal prayers, Quranic recitations, public speaking) successfully embedded key religious dimensions like belief, ritual, and moral practice in students' spiritual habits. However, critical challenges were identified: limitations in consistent evaluation and follow-through. The study recommends systematic evaluations and enhanced program designs to maximize impact on spiritual consciousness. The original contribution lies in the comprehensive application of religious dimensions to evaluate educational outcomes.